Neuroprotective Potential of Pituitary Adenylate Cyclase Activating Polypeptide in Retinal Degenerations of Metabolic Origin - Gábriel, Robert; Pöstyéni, Etelka; Dénes, Viktória (Frontiers in Neuroscience, 2019)
Pituitary adenylate cyclase-activating polypeptide (PACAP1-38) is a highly conserved member of the secretin/glucagon/VIP family. The repressive effect of PACAP1-38 on the apoptotic machinery has been an area of active research conferring a significant neuroprotective potential onto this peptide. A remarkable number of studies suggest its importance in the etiology of neurodegenerative disorders, particularly in relation to retinal metabolic disorders. In our review, we provide short descriptions of various pathological conditions (diabetic retinopathy, excitotoxic retinal injury and ischemic retinal lesion) in which the remedial effect of PACAP has been well demonstrated in various animal models. Of all the pathological conditions, diabetic retinopathy seems to be the most intriguing as it develops in 75% of patients with type 1 and 50% of patients with type 2 diabetes, with concomitant progression to legal blindness in about 5%. Several animal models have been developed in recent years to study retinal degenerations and out of these glaucoma and age-related retina degeneration models bear human recapitulations. PACAP neuroprotection is thought to operate through enhanced cAMP production upon binding to PAC1-R. However, the underlying signaling network that leads to neuroprotection is not fully understood. We observed that (i) PACAP is not equally efficient in the above conditions; (ii) in some cases more than one signaling pathways are activated; (iii) the coupling of PAC1-R and signaling is stage dependent; and (iv) PAC1-R is not the only receptor that must be considered to interpret the effects in our experiments. These observations point to a complex signaling mechanism, that involves alternative routes besides the classical cAMP/protein kinase A pathway to evoke the outstanding neuroprotective action. Consequently, the possible contribution of the other two main receptors (VPAC1-R and VPAC2-R) will also be discussed. Finally, the potential medical use of PACAP in some retinal and ocular disorders will also be reviewed. By taking advantage of, low-cost synthesis techonolgies today, PACAP may serve as an alternative to the expensive treatment modelities currently available in ocular or retinal conditions.